Endangered - Flach, Tim; Baillie, Jonathan; Wells, Sam (Abrams, 2017)
In Endangered, the result of an extraordinary multiyear project to document the lives of threatened species, acclaimed photographer Tim Flach explores one of the most pressing issues of our time. Traveling around the world--to settings ranging from forest to savannah to the polar seas to the great coral reefs--Flach has constructed a powerful visual record of remarkable animals and ecosystems facing harsh challenges. Among them are primates coping with habitat loss, big cats in a losing battle with human settlements, elephants hunted for their ivory, and numerous bird species taken as pets. With eminent zoologist Jonathan Baillie providing insightful commentary on this ambitious project, Endangered unfolds as a series of vivid, interconnected stories that pose gripping moral dilemmas, unforgettably expressed by more than 180 of Flach's incredible images.